Dekonstruksi Konsep Bahagia Kapitalis Melalui Matius 5:3 - Jansen Hutabarat; Selamat Siregar (Majalah Ilmiah METHODA, 2025)
This study examines Matthew 5:3 as a theological critique of the capitalist notion of happiness. Through a multidisciplinary approach that integrates biblical exegesis, semantic analysis of the Greek text, socio-economic philosophy, and contextual theology, the research argues that the Beatitude challenges the reduction of happiness to material possession. The Greek expression ‘makarioi hoi ptōchoi tō pneumatic’ demonstrates that “blessedness” is not simply an emotional or psychological state but a theological condition rooted in radical dependence on God. In contrast, capitalist thought as articulated by Adam Smith, Max Weber, Milton Friedman, and Ayn Rand—defines happiness in terms of wealth accumulation, market freedom, and individual self-interest, which in practice generates inequality, alienation, and systemic exploitation. As a counter-narrative, Karl Marx, Friedrich Engels, and Antonio Gramsci emphasize happiness as inseparable from social justice, solidarity, and the liberation from structural oppression. Similarly, theological voices from both liberal (Schleiermacher, Bultmann) and orthodox traditions (Chrysostom, Barth) reject the commodification of happiness, affirming instead that authentic joy is realized in communion with God and others. Employing Derrida’s theory of deconstruction, the study highlights how Matthew 5:3 subverts capitalist hierarchies by declaring the poor and marginalized as truly blessed. The findings suggest that this Beatitude should be understood not only as a spiritual affirmation but also as an ethical-political resource for critiquing modern systems of economic domination.